Party Dynasty: A Case Study of Nepotism in the Upper Echelons of Party Leadership - Muzahid Akbar Hayat; Akhyar Rifani; Ingrid Felicia; Muhammad Iqbal; Salsabila Imani Putri (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The phenomenon of political dynasties within Indonesian political parties reflects the strengthening of internal oligarchies and the weakening of party democratization. This study aims to analyze the practices of nepotism and family-based power reproduction within major political parties during the 2021–2025 period. Using a qualitative approach and a case study method, this research examines the forms of structural position inheritance, kinship-based recruitment mechanisms, and their impacts on the quality of democracy. Data were collected through literature reviews, legal document analysis, and academic studies related to political dynasties. The findings indicate that approximately 23.8 percent of members of the House of Representatives elected in the 2024 General Election have kinship ties with previous political figures, highlighting the dominance of patrimonial and patronage-based practices within major parties. The main factors driving political dynasties include efforts by incumbent elites to preserve power, the formation of exclusive groups, and restrictions on access to strategic positions for political actors outside the ruling families. This condition undermines meritocracy, contributes to internal democratic deficits, and increases the risks of nepotism and corruption. The study concludes that political party reform is urgently needed to establish transparent and competence-based recruitment and succession systems.